A Case of Pseudogout with Acute Polyarthritis - Ömer Faruk Şendur,; Gülcan Gürer,; Cavidan Ay, (Archives of Rheumatology, 2006)
In this study, we report a case of pseudogout with acute polyarthritis. A 59 years old woman was admitted with multiple joint pain. Her plain radiographs of shoulder, hip, symphysis pubis and knee showed chondrocalcinosis. She was diagnosed as pseudogout and treated with colchicine upon the finding of high levels of erythrocyte sedimentation rate and C-reactive protein in laboratory assessment and calcium pyrophosphate dehydrate crystals (CPPD) in analysis of synovial fluid under polarized light microscopy. Her complaints regressed with treatment. Pseudogout disease has been revised in the context of this case and current literature. (Rheumatism 2006; 21: 80-3)